HOLISTIC LINGUISTICS INTEGRATION IN THE REVITALIZATION OF WARA’ DANCE: INNOVATIONS FOR CREATIVE ECONOMY DEVELOPMENT AND TOURISM PACKAGES IN THE TALAUD ISLANDS REGENCY - Lalira, James; Sjerly Maria Lumi; Yopie A. T. Pangemanan; Jane Elvira Scipio; Barrylyn S. H. Kussoy; Morshe E. Lumansik; Jola Silvana Kalangi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the revitalization of Wara’ dance in the Talaud Islands Regency through a holistic linguistic approach, aiming to transform it into a dynamic cultural tourism product and a driver of the local creative economy. For over three decades, Wara’ dance has experienced stagnation, perceived as outdated and disconnected from contemporary audiences, leading to declining community participation and diminished economic returns. To address this, the research employs a qualitative method with holistic discourse analysis, integrating linguistic, anthropological, and cultural studies perspectives. Data were collected through in-depth interviews, focus group discussions, participatory observation, and analysis of archival and linguistic materials in Arangkaa Village, the historical site of King Larenggam’s resistance. The findings reveal that the dance’s verbal elements are minimal, relying on a few ritual phrases. However, rich cultural meanings are embedded in local language, toponyms like “Arangkaa” (meaning “charcoal”), and customary utterances from rituals such as Manaroho Raho. These elements were systematically analyzed and reinterpreted to innovate choreography, costumes, music, and narrative structure. A new thematic concept, “From Resistance to Revival,” was developed, enhancing the dance’s storytelling capacity and emotional depth. Community participation was central, ensuring cultural authenticity and social acceptance of the changes. The study concludes that a linguistically grounded, participatory approach enables meaningful revitalization, transforming Wara’ dance from a static tradition into a living, relevant art form. Furthermore, the proposed cultural tourism package demonstrates significant potential for generating sustainable income for performers and the local community, positioning the dance as a catalyst for both cultural preservation and economic empowerment in a remote island region.